Peran Komunikasi Efektif dalam Pembentukan Karakter Anak Usia Dini - Nur Mukhtahira; Sri Sukma; Mufaroah Mufaroah (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Effective communication plays a very important role in forming the character of early childhood. This research method uses the type of research used in this research is library research, because it is carried out by utilizing literature from previous research using various literature, articles, books, notes, magazines, other references, as well as relevant previous research results. to obtain responses and theoretical basis regarding the problem under study. The aim of this research is to determine the role of effective communication in forming the character of early childhood, to find out the factors that influence the implementation of effective communication in the environment in early childhood, and to find out the obstacles in implementing effective communication in the environment in early childhood. The research results show that effective communication is very important in the development of early childhood, helping them manage emotions, understand other people's feelings, and internalize moral values. Good communication strengthens emotional connections between children, parents, and educators, and supports social skills and critical thinking. Conversely, a lack of effective communication can hinder understanding of values ​​and influence children's behavior. Children's speaking abilities are influenced by the environment, training and guidance. Barriers arise from health, intelligence, socioeconomics, and communication style. Parents' positive communication patterns encourage children's development, while negative styles hinder it.